2014
DOI: 10.1002/mats.201300166
|View full text |Cite
|
Sign up to set email alerts
|

Development of Molecular Weight Distribution in ATRP with Radical Termination

Abstract: In a previous work, a model of full molecular weight distribution (MWD) for atom transfer radical polymerization with radical termination has been developed, using analogy to a series of continuous stirred tank reactors. This model assumes constant reaction rates, which is applicable to low conversion batches or steady-state continuous processes. In this work, the model is generalized to any polymerization condition, which provides variations of the reaction rates with conversion are known. Using this extended… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 59 publications
1
20
0
Order By: Relevance
“…Considering the chain termination reaction, M n decreases from 40 904 to 40 060, whereas PDI increases from 1.025 to 1.047. Similar simulation results are also reported by Mastan et al 28; accumulation of oligomers in the system may be a possible reason for these results. In addition, the dead polymer is mainly generated close to the reactor wall and far from the reactor inlet (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…Considering the chain termination reaction, M n decreases from 40 904 to 40 060, whereas PDI increases from 1.025 to 1.047. Similar simulation results are also reported by Mastan et al 28; accumulation of oligomers in the system may be a possible reason for these results. In addition, the dead polymer is mainly generated close to the reactor wall and far from the reactor inlet (see Fig.…”
Section: Resultssupporting
confidence: 91%
“…If needed, inversion method can be applied to construct the full CLD based on the premise that the distribution type is known. Furthermore, Mastan et al recently proposed a novel method for the description of full molar mass distribution of polymer synthesized by ATRP . The novelty of that work lies in analogously relating the activation–deactivation cycles in ATRP to a series of CSTRs.…”
Section: Methods Of Momentsmentioning
confidence: 99%
“…In this work, diffusional limitations on termination were ignored for simplicity. Subsequently, a modified model for monomer conversion dependent PDI and a new polydispersity expression including effects of the monomer conversion, monomer addition per activation/deactivation cycle, and amount of dead chains were introduced for ATRP systems . Saldívar‐Guerra et al showed that direct integration of the equation can be used to predict the CLD for NMP and RAFT polymerization systems …”
Section: Methods Of Momentsmentioning
confidence: 99%
“…The polymer MWD can be better understood and controlled by using mathematical models that describe its evolution during the synthesis reaction. Previous mathematical modeling of ATRP has been done by a number of research groups, but most of that research focused on previous versions of ATRP, especially early works trying to better understand the kinetics and mechanism of these processes. In contrast, a few have been done on the modeling of ICAR and ARGET systems, which have greater industrial potential.…”
Section: Introductionmentioning
confidence: 99%